2001
DOI: 10.1038/sj.ejcn.1601275
|View full text |Cite
|
Sign up to set email alerts
|

Wintertime vitamin D insufficiency is common in young Canadian women, and their vitamin D intake does not prevent it

Abstract: Objective: We asked whether women self-reporting the recommended consumption of vitamin D from milk and multivitamins would be less likely to have low wintertime 25-hydroxyvitamin D (25(OH)D) levels. Methods: This cross-sectional study enlisted at least 42 young women each month (age 18 -35 y, 796 women total) through one year. We measured serum 25(OH)D and administered a lifestyle and diet questionnaire. Results: Over the whole year, prevalence of low 25(OH)D ( < 40 nmol=l) was higher in non-white, non-black … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
157
2
7

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(180 citation statements)
references
References 41 publications
14
157
2
7
Order By: Relevance
“…Four other studies focused on the vitamin D status of Canadians (25,(36)(37)(38), of which two were conducted in young women in Ontario (latitude 438N) (36,37) and one in teenage girls from Québec (38). Vieth et al (36) recruited 796 women aged 18-35 years sampled once over a year.…”
Section: Discussionmentioning
confidence: 99%
“…Four other studies focused on the vitamin D status of Canadians (25,(36)(37)(38), of which two were conducted in young women in Ontario (latitude 438N) (36,37) and one in teenage girls from Québec (38). Vieth et al (36) recruited 796 women aged 18-35 years sampled once over a year.…”
Section: Discussionmentioning
confidence: 99%
“…The vitamin D concentrations found in the present study were low for the majority of the participants and, thus, contradict the anecdotal assumption that vitamin D status in north Norway is satisfactory (5). Since sunshine exposure has been considered to be the main source of vitamin D, its status is known to drop during winter and improve during summer months (16)(17)(18)(19). Lehtonen-Veromaa et al (7) found a prevalence of 25(OH)D levels ≤ 37.5 nmol/L in excess of sixty percent during winter, which reduced to less than two percent during the summer among 15-year-old Finnish girls in Turku, Southwest Finland.…”
Section: Discussionmentioning
confidence: 99%
“…An early study of young women (18-35 years of age) in Toronto found that in winter, 21% of white women, 32 of non-white women (a group which combined First Nations peoples, South Asian, Indo Asian, and East Asian ancestries), and 25% of black women had serum concentrations below 40 nmol/L [126].…”
Section: North Americamentioning
confidence: 99%
“…For example, Vietnamese immigrants in Norway were reported to have lower prevalence of hypovitaminosis D compared to Turkish or Pakistani immigrants [40]. In Canada, young women from Asian and to a lesser extent, African origins, showed lower levels of vitamin D compared to whiteCanadian women [126]. In the USA, African Americans, then Mexican Americans, showed more severe vitamin D deficiency compared to non-Hispanic white Americans [122].…”
Section: Genetic Traits and Cultural Behaviourmentioning
confidence: 99%